Lecture capture, social topology, and the spatial and temporal arrangements of UK universities. (November 2022) - Lamb, James; Ross, Jen
This article considers how technologies actively shape the topologies of UK higher education. Using the example of lecture capture systems, we examine the relationship between learning technologies and formations of space and time. Combining theories of sociomateriality and social topology, and concepts of assemblage and relationality, we expose the entanglement of interests that influence university spaces and times. Across 3 months coinciding with the onset of COVID-19 we collected over 500 tweets that discussed lecture capture within UK higher education, leading towards 2 central arguments. First, the topology of the lecture is fluid, and, even while being radically technologised, re-spatialised and disrupted, it persists as a lecture and a central pedagogical feature of university life. Second, lecture capture is a rich site of 'issuefication', and viewing learning technologies as dynamic issues enables a better understanding of how their meaning, function and influence are contingent on shifting and relational assemblages of human and non-human interests. Lecture capture can be pedagogical, commercial and political, thereby resisting deterministic framings of the relationship between technologies and the temporal and spatial arrangements of higher education.